Land Certificate Making Services at the Agrarian and Spatial Planning Office/National Land Agency of Gowa Regency - Haedar Akib; Raodatul Jannah; Putri Abadi Handayani; Muh Darwis (Journal of Social Science and Economics (JOSSE), 2024)
Service is every effort that is carried out/provided in order to meet the needs of those who need it, both in the form of goods and services. The purpose of this study is to find out the services for making land certificates at the Agrarian and Spatial Planning office/National Land Agency of Gowa Regency. To find out the purpose of the research, a qualitative descriptive type of research is used. The informants in this study were 3 people using data collection techniques through observation, interviews, and documentation. The data obtained from the results of the research was then processed using data analysis techniques consisting of data reduction, data presentation, and conclusion drawn. The results of the study show that the land certificate making service at the Agrarian and Spatial Planning office/National Land Agency of Gowa Regency is good with all indicators and is considered adequate.